(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In order to study the clinical and epidemiological manifestations of acute brucellosis, 82 patients were examined. The age of the examined patients ranged from 19 to 60 years. The diagnosis was based on the results of a comprehensive analysis of epidemiological and anamnestic data, clinical manifestations of the disease and laboratory tests (in all patients, the diagnosis was established on the basis of serological data), which made it possible to identify the clinical and epidemiological features of this disease at the present stage